PERAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER SISWA - Muslem Muslem (Lembaga Sepercenter, 2025)
Islamic Religious Education (IRE) plays a vital role in shaping students’ character amidst an increasingly complex world. Education serves not only to enhance learners’ intellectual abilities but also aims to foster individuals of noble character who are responsible, disciplined, and possess strong moral values. This article discusses the role of Islamic Religious Education in shaping students’ character through the instilling of religious values, the cultivation of positive behaviour, and the exemplary conduct of teachers in the learning process. The method used in this article is a literature review, examining various scientific sources related to character education and Islamic Religious Education. The findings indicate that Islamic Religious Education can serve as a primary foundation in shaping students’ character through the values of honesty, responsibility, discipline, tolerance, and social concern. Therefore, the implementation of Islamic Religious Education must be carried out comprehensively within the school environment, the family, and the wider community to ensure that national educational objectives are achieved optimally.